Molecular mechanisms of the effects of photodynamic therapy on the brain: A review of the literature - Paweł Woźnicki; Dorota Bartusik-Aebisher; Agnieszka Przygórzewska; David Aebisher (Photodiagnosis and Photodynamic Therapy)
Malignant gliomas are the most common primary brain tumors in adults. These tumors have a diverse molecular origin and a very poor prognosis. There is a lack of effective treatment at WHO grade IV glioma, and all glioblastomas progress or recur. Current treatments including surgical intervention, radiation therapy, and chemotherapy are insufficient and can cause damage to healthy brain tissue and neurological deficits. The preservation of healthy brain tissue during therapeutic intervention is made extremely difficult by the ability of malignant gliomas to diffusely infiltrate the surrounding brain parenchyma. Photodynamic therapy (PDT) is a treatment modality for glioma that can possibly overcome the inherent shortcommings of traditional therapies. Photodynamic therapy involves the use of a photosensitizer (PS) which, upon absorption of light by photosensitized tissue, triggers photochemical reactions generating reactive oxygen species (ROS) leading to the killing of tumor cells. Research focusing on the effective use of PDT in the treatment of glioma is already underway with promising results. Clinical studies on PDT for the treatment of gliomas have shown it to be a safe therapeutic modality with acceptable levels of side effects. However, some adverse sequelae have been observed during PDT of these tumours, such as increased photosensitivity, increased intracranial pressure or transient aphasia and worsening of pre-existing neurological deficits. Although the clinical sequelae of PDT are well described, the molecular mechanisms of PDT's effects on the healthy brain have not yet been thoroughly characterized. In our work, we attempt to summarize the molecular mechanisms of the effects of photosensitization on neural tissue, brain vasculature and the blood-brain barrier (BBB). We also point to findings presenting molecular approaches to protect the healthy brain from the adverse effects of photodynamic damage.